An Observer With Cooperative Interaction Structure for Biasing Attack Detection and Secure Control - Huang, Xin; Li, Jian; Su, Qingyu (IEEE transactions on systems, man, and cybernetics. Systems, 2023)
This article studies state estimation and attack reconstruction problems for sensor and actuator biasing attack detection and secure control in cyber-physical systems (CPSs) through the observer techniques. The considered unknown bounded biasing attacks are produced from any dynamical system satisfying the error system between it and its equilibrium to be input-to-state stable, so that some reported biasing attacks are contained as a special case. In order to deal with potential compromised sensor output signals, an auxiliary filter is first introduced. Then, an augmented system, including the CPS and filter dynamics is constructed. Furthermore, with the aid of the system structure and input-output data, fictitious systems comprising the information of attack reconstruction errors are given. And then, by the cooperative interaction between the dynamics of observer's estimation errors and virtual systems, an observer with a cooperative interaction structure is proposed, where the fictitious systems can be viewed as co-workers conducing to the accurate state estimation and attack reconstruction. By the Lyapunov approach, it is shown that state estimations and reconstructed attack signals, respectively, converge to the small set around system states and real attack signals, and the set bound can be reduced by adjusting the observer's parameter. The applications of the observer to biasing attack detection and secure control are further given. Finally, an illustrative example validates the proposed methods.